Analisis Citraan Pada Terjemahan Novel Al-Fatá al-ladhi Absara Lawnu al-Hawa: Tinjauan Stilistika - Ismail, Asnia Rahmawati; Wahyudi, Arif; Asnania, Aisya Putri; Satori, Achmad; Nurhuda, Zamzam; Suparno, Darsita (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2023)
The research examines the issue of imagery in the translation of the novel